A Patient-Specific Reference Tracker for Noninvasive Electromagnetic Navigation of Endoscopic Skull Base Surgery. Issue 6 (7th December 2022) - Micko, Alexander; Minchev, Georgi; Wurzer, Ayguel; Kronreif, Gernot; Wolfsberger, Stefan
Abstract : BACKGROUND: Owing to the possibility of nonrigid head fixation, electromagnetic navigation (EM) is a mainstay for endoscopic skull base surgery. The currently available dynamic reference trackers (RTs) are invasive or inaccurate. OBJECTIVE: To investigate the feasibility and stability of this innovative oral tracker (OT), which is adhesive to the hard palate in comparison with a commercially available skin adhesive tracker (ST). METHODS: A prospective series of 31 patients with intrasellar lesions who underwent surgery between 2019 and 2021 using a pure endoscopic transsphenoidal approach were evaluated. A patient-specific palatal mold was designed from preoperative computed tomography data. The OT was cast using a biocompatible algin with an integrated EM tracker assembly. In comparison with a skull-mounted RT, which served as a gold standard, the deviations of OT vs those of the ST with the RT were continuously assessed. RESULTS: The OT showed significantly lower deviations from the RT than the ST during the surgical steps: start of endoscopic surgery (OT vs ST: 0.62 mm, IQR 0.36-0.89 vs 1.65 mm, IQR 1.35-2.32, P < .001), drilling phase (OT vs ST: 0.81 mm, IQR 0.51-1.32 vs 1.89 mm, IQR 1.6-2.74, P < .001), and end of endoscopic surgery (OT vs ST: 1.1 mm, IQR 0.68-1.64 vs 1.9 mm, IQR 1.6-2.72, P < .001). CONCLUSION: The OT showed significantly higher intraoperative stability than the ST. Therefore, this noninvasive and patient-specific tool could be used to achieve accurate EM guidance during endoscopic skull base surgeries.